Os limites morais do Estado em face da Teoria da titularidade, em Robert Nozick - Diniz, Nikolas Cirilo (2019)
The present work aims to show the Political Philosophy by Robert Nozick regarding to the moral boundaries imposed on political authority. Thereunto, it was resorted to historical bases exposure that influenced Nozick and how they were articulated throughout his political thinking. According Nozick, the moral philosophy circumscribes the political philosophy, i.e., all the actions boundaries imposed by morality are not limited just to the figure of the individual, but are equally applicable to political authority. Therefore, Nozick's philosophy includes the elaboration of moral theories aiming to substantiate the limits of the political sphere. Thus, following to the introduction and development of the theory of Moral Side Constraint and Entitlement Theory, both elaborated by Robert Nozick in the work Anarchy, State and Utopia, and which operate in their philosophy as moral boundaries to the State actions